PENGARUH GAYA BELAJAR EXPERIENTIAL LEARNING DALAM PENINGKATAN PRESTASI AKADEMIK DAN PENERAPANNYA DALAM PEMBELAJARAN - - Sugiyanto (Paradigma, 2013)
Abstract. Teachers in the learning process, should pay attention to the characteristics of their students. A wide range of student characteristics, both internally and externally. One of the characteristics of students in learning that need to be considered in teacher learning and affect the effectiveness of teaching and learning is the learning styles of the students.Experiential Learning not only provide insight into the concepts of knowledge alone. However, it also gives a real experience that will build skills through real assignments. Experienced learning theory is formed through a process of suppression. Suppression process includes concrete experience, observe /reflect on concrete experiences, abstract concepts and generalizations formatting, to test implications of concepts in new situations. The four processes form the four types of learning styles are: konverger, akomodator, diverger, and assimilator.Teachers in teaching has its own learning style as well as the types of students have learning styles but it does not mean the quality of teaching by itself will increase. Learning style is closely related to an individual's personal history influenced by education and development. This is because the factors that affect academic achievement itself. Therefore, in the learning process teachers need to pay attention to the types of learning styles of the students as well as teachers also have their own learning style.